Observations of the April 2002 geomagnetic storm by the global network of incoherent scatter radars - Goncharenko, L. P. (2005)
This paper describes the ionospheric response to a geomagnetic storm beginning on 17 April 2002. We present the measurements of ionospheric parameters in the F-region obtained by the network of eight incoherent scatter radars. The main effects of this storm include a deep decrease in the electron density observed at high and middle latitudes in the pre-noon sector, and a minor enhancement in the density observed in the daytime sector at middle latitudes. Extreme plasma heating (>1000-3000 K) is observed at high latitudes, subsiding to 200-300K at subauroral latitudes. The western hemisphere radar chain observed the prompt penetration of the electric field from auroral to equatorial latitudes, as well as the daytime enhancement of plasma drift parallel to the magnetic field line, which is related to the enhancement in the equatorward winds. We suggest that in the first several hours after the storm onset, a negative phase above Millstone Hill (pre-noon sector) results from counteracting processes - penetration electric field, meridional wind, and electrodynamic heating, with electrodynamic heating being the dominant mechanism. At the lower latitude in the pre-noon sector (Arecibo and Jicamarca), the penetration electric field becomes more important, leading to a negative storm phase over Arecibo. In contrast, in the afternoon sector at mid-latitudes (Kharkov, Irkutsk), effects of penetration electric field and meridional wind do not counteract, but add up, leading to a small (~15%), positive storm phase over these locations. As the storm develops, Millstone Hill and Irkutsk mid-latitude radars observe further depletion of electron density due to the changes in the neutral composition.